Passiflora intricata, an apetalous new species from the Dominican Republic in Supersection Auriculatae (Passifloraceae) - Macdougal, John M.; Ochoa, Jorge; Krosnick, Shawn E. (Phytotaxa, 2018)
A new species of Passiflora L. endemic to the Dominican Republic, P. intricata, is described and illustrated from herbarium material and living plants. The flower is unusual in Passiflora by its vestigial androgynophore and tangled thread-like corona. It is placed in subgenus Decaloba supersection Auriculatae s.str. on the basis of its plicate operculum, laminar and petiolar nectaries, grooved seeds, very reduced petals (absent in this new species) and apically attenuate coronal filaments.